Exploring the Antioxidant and Structural Properties of Black Bean Protein Hydrolysate and Its Peptide Fractions - Chen, Yin; Zheng, Zhaojun; Ai, Zixuan; Zhang, Yan; Tan, Chin Ping; Liu, Yuanfa (Frontiers in Nutrition, 2022)
Bromelain has been commonly used to hydrolyze black bean protein via response surface methodology (RSM). The optimal hydrolysis parameters were observed at 52 °C, pH 7, E/S ratio of 2.2, and 4 hours. Under these parameters, the hydrolysate (BPH) presented DPPH radical scavenging activity and Fe2+ chelating activity with IC50 values of 100.08 ± 2.42 and 71.49 ± 0.81 μg/mL, respectively. This might be attributed to structural characteristics, varying with different molecular weight distributions. Interestingly, among BPH and its peptide fractions, peptides smaller than 3 kDa were noted to exhibit the strongest DPPH and ABTS radical scavenging activity. This may be due to high proportions of hydrophobic amino acids. Unexpectedly, the optimal Fe2+ chelating activity was observed in the peptide fraction measuring at 3–10 kDa, showing highly positive correlations with histidine and arginine. These identified peptide fractions derived from black bean protein can therefore be employed for food fortification acting as natural antioxidant alternatives.